Limiting oil imports : an economic history and analysis - Bohi, Douglas R.; Russell, Milton; Resources for the Future (Baltimore : Published for Resources for the Future by the Johns Hopkins University Press, 1978)
This book presents the results of the third phase of our analysis of U.S. oil imports in relation to U.S. energy policy. Our research began with a grant from Resources for the Future in early 1973.
Includes bibliographical references and index.
gau 13/02/17
Loans
Keywords: Petroleum industry and trade; Import quotas; Energy policy